2005
DOI: 10.1088/1464-4266/7/12/024
|View full text |Cite
|
Sign up to set email alerts
|

Matter-screened Casimir force and Casimir–Polder force in planar structures

Abstract: Abstract. Using a recently developed theory of the Casimir force (Raabe C and Welsch D-G 2005 Phys. Rev. A 71 013814), we calculate the force that acts on a plate in front of a planar wall and the force that acts on the plate in the case where the plate is part of matter that fills the space in front of the wall. We show that in the limit of a dielectric plate whose permittivity is close to unity, the force obtained in the former case reduces to the ordinary, i.e., unscreened Casimir-Polder force acting on iso… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…We find scenarios where the Casimir force between the plates and the forces due to the presence of the atoms oppose each other, so that in certain regimes the total force between the plates can become repulsive. This result from a microscopic description supports previous works that used macroscopic effective models, suggesting that Casimir forces can be screened in the presence of matter [24,25].…”
Section: Arxiv:13117619v2 [Quant-ph] 21 Mar 2014supporting
confidence: 90%
See 2 more Smart Citations
“…We find scenarios where the Casimir force between the plates and the forces due to the presence of the atoms oppose each other, so that in certain regimes the total force between the plates can become repulsive. This result from a microscopic description supports previous works that used macroscopic effective models, suggesting that Casimir forces can be screened in the presence of matter [24,25].…”
Section: Arxiv:13117619v2 [Quant-ph] 21 Mar 2014supporting
confidence: 90%
“…This can be seen in both plots of Fig. 5, for the interaction Hamiltonians ( 23) and (24), i.e., with and without the diamagnetic term. Also, once again, the attractive forces in the UdW case turn repulsive when including the diamagnetic term.…”
Section: An Atom In a Neumann-type Cavitymentioning
confidence: 63%
See 1 more Smart Citation
“…It may appear surprising that this rather complicated 5-layered geometry is chosen, as it adds considerable mathematical complications as compared to the simpler three-layer geometry considered by Lifshitz [25] and later by numerous others. A slightly simpler geometry of a slab of finite width outside a half-space was subsequently considered [26,27] and it was shown that a modified Casimir-Polder force [28] was obtained in the case where the slab is a slice of the same dilute medium as fills the interspace.…”
Section: The Casimir Force As Predicted By Raabe-welschmentioning
confidence: 99%
“…If, as proposed in [26], the Raabe Welsch force may be thought of as Casimir-Polder forces acting on particles in the interspace medium, such similarity could make physical sense since also the Casimir-Polder force diverges with vanishing separation.…”
Section: The Casimir Force As Predicted By Raabe-welschmentioning
confidence: 99%